2009
DOI: 10.3113/fai.2009.1101
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Platelet-Rich Plasma on Angiogenesis During the Early Phase of Tendon Healing

Abstract: Although these results need replication and further biomechanical research, PRP may promote tendon healing acceleration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
92
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(102 citation statements)
references
References 30 publications
6
92
0
4
Order By: Relevance
“…The multimolecular preparations, obtained from autologous blood, provide clinical benefits by modulating the early healing response through secretion of an array of signaling cytokines that influence inflammation and angiogenesis concurrently and influence cell migration and proliferation [10,13,23,24]. Plateletrich plasma affects healing, both physiologically and pathologically, and is currently used not only in surgery [2,16], but also as an injectable to treat pathological conditions such as osteoarthritis (OA) and tendinopathies [5,6,14], in which the disordered vascularization and deleterious neoinnervation are associated with reduced healing capability and increased vulnerability to chronic injuries.…”
Section: Introductionmentioning
confidence: 99%
“…The multimolecular preparations, obtained from autologous blood, provide clinical benefits by modulating the early healing response through secretion of an array of signaling cytokines that influence inflammation and angiogenesis concurrently and influence cell migration and proliferation [10,13,23,24]. Plateletrich plasma affects healing, both physiologically and pathologically, and is currently used not only in surgery [2,16], but also as an injectable to treat pathological conditions such as osteoarthritis (OA) and tendinopathies [5,6,14], in which the disordered vascularization and deleterious neoinnervation are associated with reduced healing capability and increased vulnerability to chronic injuries.…”
Section: Introductionmentioning
confidence: 99%
“…Rat models have shown that PRP increases tendon strength 24 when injected locally. In rabbit Achilles tendons, increased vascularity and better tissue organization have been found 11 . Moreover, one clinical study comparing PRP treated patients with historical controls has indicated that peroperative PRP treatment allows earlier return to sports 17 .…”
Section: Introductionmentioning
confidence: 99%
“…16 Experimental studies on PRP suggested a potential benefit of PRP in enhancing the healing process by activating neovascularization in areas with poor vascularity. 17 Another experimental model support that platelet-rich fibrin matrix (an alternative preparation of similar properties) enhances endothelial cell proliferation. This may provide an explanation of wound healing effect of PRP.…”
Section: Discussionmentioning
confidence: 99%